2020
DOI: 10.1001/jamanetworkopen.2020.7539
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of a Stepwise Approach vs Standard Care for Diabetes Prevention in India

Abstract: IMPORTANCE A stepwise approach that includes screening and lifestyle modification followed by the addition of metformin for individuals with high risk of diabetes is recommended to delay progression to diabetes; however, there is scant evidence regarding whether this approach is costeffective.OBJECTIVE To estimate the cost-effectiveness of a stepwise approach in the Diabetes Community Lifestyle Improvement Program. DESIGN, SETTING, AND PARTICIPANTSThis economic evaluation study included 578 adults with impaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…However, no studies were identified through forward and backward searches. Finally, 11 articles met the selection criteria and were included in the review (see Figure 1 for the PRISMA flow diagram) [ 41 , 42 , 43 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, no studies were identified through forward and backward searches. Finally, 11 articles met the selection criteria and were included in the review (see Figure 1 for the PRISMA flow diagram) [ 41 , 42 , 43 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were conducted in Bangladesh [ 48 ], China [ 47 , 52 ] including Hong Kong [ 51 ], India [ 41 , 43 , 49 ], Malaysia [ 54 ], Singapore [ 42 , 50 ], and Sri Lanka [ 53 ] with T2DM patients and participants who were at high risk of developing T2DM. Participants included in the studies were aged 5 years and above, and the average sample size of the studies was 920 participants (study samples ranged between 166 and 3539 participants).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations